Karakteristik Radiologi Foto Thorax Penderita Tuberkulosis Paru Pada Anak Di Rumah Sakit Royal Prima Medan - Larasati, Nieken Dwi; Hakim Nasution, Ikhwanul; Halim, Yeni (Syntax Literate, 2025)
This study aimed to analyze the radiological characteristics of chest X-rays in pediatric pulmonary tuberculosis (TB) patients at Royal Prima Hospital Medan. A retrospective descriptive correlational design was applied using medical records of 60 pediatric patients diagnosed with pulmonary TB during January–December 2024. The analyzed variables included age, gender, and radiological findings such as primary lesion, pleural effusion, cavity, and atelectasis. The results revealed that the majority of pediatric TB cases occurred in the 6–10 years age group (41.7%) and were more prevalent in males (58.3%). The most common primary lesion observed was infiltration (58.3%), while most patients did not present with pleural effusion (80%), cavity (86.7%), or atelectasis (83.3%). These findings indicate that pediatric TB at Royal Prima Hospital Medan predominantly affects school-aged boys, with relatively mild radiological features.